Distribusi Spasial Lamun di Perairan Sekotong Barat-TWP Gita Nada Lombok Barat Menggunakan Citra Landsat 8 OLI - Arfian Sholihin; Arben Virgota; Sri Puji Astuti; Baiq Farista; Sukiman Sukiman (Bioscientist : Jurnal Ilmiah Biologi, 2023)
West Sekotong Village is one of the coastal water areas included in the Gita Nada Aquatic Tourism Park (TWP) area which has a seagrass habitat. Seagrass beds in West Sekotong are threatened due to increased tourism and community activities. This research aims to determine the distribution and extent of seagrass beds on the coast of West Sekotong-TWP Gita Nada. This research uses a remote sensing approach through interpretation of Landsat 8 OLI imagery. This research consists of 2 steps, namely image data processing and supporting data. Image data processing includes several stages, namely image data collection, geometric correction, radiometric correction, image cutting, image composite, image data sharpening, image data interpretation, accuracy testing, area measurement, and final layout. Supporting data was obtained by searching related literature, interviews and surveys of activities that have the potential to have an impact on seagrass ecosystems. The research results show that the distribution of seagrass in West Sekotong-TWP Gita Nada covers the coast of the large island (mainland) and the coast of small islands. The distribution of seagrass on the mainland is found on the coasts of Medang, Tanjung Kelor, Batu Kijuk, Tawun, Labu, Kelapa, Pandanan, Gili Genting, Labuan Petung, Temeran, and Gawah Pudak. In the coastal areas of small islands, seagrass is found on Gili Sudak, Gili Tangkong, Gili Nanggu, Gili Poh, and Gili Lontar. The total area of seagrass beds in West Sekotong is around 144.68 ha. On the mainland coast the area is 118.96 ha (82.2%) and on small islands the area is around 25.72 ha (17.8%). The distribution of seagrass in West Sekotong is influenced by many factors, among which those observed in this research are the type of substrate, the presence of river estuaries, and the use of land and coastal waters.